Do EPs change their clinical behaviour in the hallway or when a companion is present? A cross-sectional survey. Issue 7 (3rd February 2018) - Stoklosa, Hanni; Scannell, Meredith; Ma, Zheng; Rosner, Bernard; Hughes, Ashley; Bohan, J Stephen
Abstract : Objectives: Our aim was to determine whether emergency physicians (EPs) felt their standard patient evaluation practice was modified by two non-private clinical encounters: hallway encounters and encounters during which a companion was present. Methods: We administered an iteratively developed cross-sectional survey at an annual national professional meeting. We used logistic regression to compare relationships among non-private clinical encounters and predictors of interest. Results: 409 EPs completed the survey. EPs deviated from standard history-taking when practising in a hallway location (78%) and when patients had a companion (84%). EPs altered their standard physical exam when practising in a hallway location (90%) and when patients had a companion (77%). EPs with at least a decade of experience were less likely to alter history-taking in the hallway (OR 0.55, 95% CI 0.31 to 0.99). Clinicians who frequently evaluated patients in the hallway reported delays or diagnostic error-related to altered history-taking (OR 2.34, 95% CI 1.33 to 4.11). The genitourinary system was the most common organ system linked to a delay or diagnostic error. Modifications in history-taking were linked to delays or failure to diagnose suicidal ideation or self-harm (25%), intimate partner violence (40%), child abuse (12%), human trafficking (8%), substance abuse (47%) and elder abuse (17%). Conclusions: Our study suggests that alterations in EP usual practice occurs when the doctor–patient dyad is disrupted by evaluation in a hallway or presence of a companion. Furthermore, these disruptions are associated with delays in care and failure to diagnosis medical, social and psychiatric conditions.